THE TWO EARLIEST INTERNATIONAL TREATIES IN THE HISTORY OF SLAVIC LAW - Nikolić, Dragan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The Russia-Byzantium treaties of 911 and 944 are the two earliest international agreements in the Slavic legal history, which have justifiably drawn considerable attention of legal historians since the mid-19th century. The contents of these political and trade agreements between Russia and the Byzantine Empire depict the contours of the ancient law in the early Russian state in the first century of its existence. Viewed in a wider historical context, the provisions of these agreements clearly reflect the social reality in Russia in the first half of the 10th century. Concurrently, these agreements are first-class historical sources depicting the social history of the early Middle Ages in general, as well as the sources of Byzantine, Russian and Slavic history in particular. They comprise some important facts which may be used (to some extent) in the process of reconstructing the social, economic and legal status of some categories of population. In terms of other contents, both treaties primarily contain conventional legal norms, in most cases including clearly defined dispositions and sanctions. Both treaties indicate that the social class of large merchants had already been well-established in Russia at that time, as they travelled to Constantinople in their vessels to trade in commodities. The Byzantine state guaranteed their freedom of trade, accommodation, personal safety and property security during their stay in Constantinople. The treaties contain provisions obliging the local population to provide assistance in the event a Russian or a Byzantine vessel was damaged or stranded in the territorial waters of either Russia or the Byzantine Empire. The parts of these treaties pertaining to civil law institutes show that Russian law protected private property only if one had legal ownership (title to property). We also learn that the Russian succession law had already recognized both testate and intestate succession, due to an article which prescribes as follows: if a Russian dies in the territory of Byzantium and has not made a testament, his movable property shall be returned to Russia and delivered to his next of kin. The criminal law provisions on murder, bodily injuries, common theft, robbery, and snatching or concealing a fugitive slave owned by another also included some designations on criminal proceedings. An article in the 911 Treaty specifies that the contracting states shall accept the mutual obligation to extradite to the state of origin the criminal offender apprehended in the territory of either state. Both treaties include provisions on the involvement or voluntary military service of Russian nationals in the Byzantine army, which is explicitly permitted either upon the express desire of an individual Russian citizen or upon the express summons and request of the Byzantine emperor seeking assistance of Russian soldiers in the military operations of the Byzantine army. Three articles of the 944 Treaty refer to the Kherson (Cherson) region, the ancient Byzantine colony on the Crimean Peninsula. They stipulate that the Russians are not allowed to fight in this region or impose their power on Kherson cities, nor are they permitted to let the neighboring Bulgarians fight there. It is also envisaged that the Russians shall not use force to prevent the local inhabitants of Kherson from fishing at the confluence of the Dnieper River into the Black Sea.